Incorporation of a Biocompatible Nanozyme in Cellular Antioxidant Enzyme Cascade Reverses Huntington's Like Disorder in Preclinical Model. Issue 7 (16th December 2020) - Adhikari, Aniruddha; Mondal, Susmita; Das, Monojit; Biswas, Pritam; Pal, Uttam; Darbar, Soumendra; Bhattacharya, Siddhartha Sankar; Pal, Debasish; Saha‐Dasgupta, Tanusri; Das, Anjan Kumar; Mallick, Asim Kumar; Pal, Samir Kumar
Abstract: The potentiality of nano‐enzymes in therapeutic use has directed contemporary research to develop a substitute for natural enzymes, which are suffering from several disadvantages including low stability, high cost, and difficulty in storage. However, inherent toxicity, inefficiency in the physiological milieu, and incompatibility to function in cellular enzyme networks limit the therapeutic use of nanozymes in living systems. Here, it is shown that citrate functionalized manganese‐based biocompatible nanoscale material (C‐Mn3 O4 NP) efficiently mimics glutathione peroxidase (GPx) enzyme in the physiological milieu and easily incorporates into the cellular multienzyme cascade for H2 O2 scavenging. A detailed computational study reveals the mechanism of the nanozyme action. The in vivo therapeutic efficacy of C‐Mn3 O4 nanozyme is further established in a preclinical animal model of Huntington's disease (HD), a prevalent progressive neurodegenerative disorder, which has no effective medication to date. Management of HD in preclinical animal trial using a biocompatible (non‐toxic) nanozyme as a part of the metabolic network may uncover a new paradigm in nanozyme based therapeutic strategy. Abstract : Citrate functionalized Mn3 O4 nanoparticles can mimic glutathione peroxidase (GPx) to treat Huntington's like severe neurobehavioral toxicity in experimental animals. The nanoparticles are biocompatible, can efficiently function in the physiological milieu, and possess the unique ability to be incorporated into the cellular enzyme cascade. Successful human trials will impart a new regime in treatment of neurodegenerative disorders like Huntington's, Parkinson's, Alzheimer's, etc.